Metode Weighted Product Pada Penentuan Perjalanan Dinas ( Studi Kasus : Arsip Nasional Republik Indonesia ) - Riki Ruli A. Siregar; Anugrah Danny Prasetyo (Sekolah Tinggi Teknik - PLN, 2016)
The determination of employee uses an alternative method to produce a decision. Methods for generating decision alternatives for employees who are entitled to travel is the method of Weighted Product. Weighted Methods Product has a consistent pattern in its calculation formula so that the calculation formula kesederhanan remains stubbornly high accuracy to four decimal places. determination of weighting between the criteria of benefit and cost criteria are within the powers of formula distinguishing numbers with positive and negative values ​​so the calculation becomes easier. Simplicity in calculation and the value of high accuracy is needed because the predefined criteria of ten criteria so that the result is very selective. This research was placed as a tool which is used prior to decision-making, for the alternative decision in determining employees in following official travel based on the criteria. This application required for the emergence of budget problems are less, the use of the budget surplus of the budget is predetermined. With this application, is expected to assist in the administration of official travel and provide the first step in saving and adjusting travel budgets in each of its parts.